Determining legal responsibilities in defamation: crossing the dividing line between real world and internet jurisdiction (2017)
Defamation is a recognised exception to the exercise of right to freedom of expression under the law. With the advent of the Internet, defamatory statements can be communicated or published with seamless ease and having their consequences in geographically locatable territories. The Internet as a new and more effective medium of communication compared to the traditional communication systems, like newspapers, tabloids, letters, etc. presents special challenges to the existing legal regime for traditional defamation law, which include the determination of legal responsibilities of parties involved in the defamation matter and the problem of jurisdiction- given the ubiquitous nature of the Internet. This paper therefore seeks to address the peculiar challenges posed by this new medium, especially as to the phenomenon of ‘publication ’ in determining the responsibilities of parties on the Internet and also the issue of court’s jurisdiction in internet defamation. The paper will particularly engage the laws and approaches in some countries, especially the United Kingdom, the United State of America, Malaysia, India, China, Australia, Argentina and Nigeria, to identify the similarities and dissimilarities in their defamation legal regimes; and also to review the approaches adopted in addressing internet defamation. Nigeria in particular does not have specialised legal response to internet defamation just like many other developing jurisdictions. This paper seeks to address and analyse the approaches in other jurisdictions and distil a harmonious approach that can be adopted to address the deficit created in defamation laws in some jurisdictions that do not have legal response to internet based defamation.